GUMICS-4 analysis of interplanetary coronal mass ejection impact on Earth during low and typical Mach number solar winds - Lakka A; Pulkkinen TI; Dimmock AP; Kilpua E; Ala-Lahti M; Honkonen I; Palmroth M; Raukunen O (COPERNICUS GESELLSCHAFT MBH, 2022)
We study the response of the Earth's magnetosphere to fluctuating solar wind conditions during interplanetary coronal mass ejections (ICMEs) using the Grand Unified Magnetosphere-Ionosphere Coupling Simulation (GUMICS-4). The two ICME events occurred on 15-16 July 2012 and 29-30 April 2014. During the strong 2012 event, the solar wind upstream values reached up to 35 particles cm(-3), speeds of up to 694 km s(-1), and an interplanetary magnetic field of up to 22 nT, giving a Mach number of 2.3. The 2014 event was a moderate one, with the corresponding upstream values of 30 particles cm(-3), 320 km s(-1) and 10 nT, indicating a Mach number of 5.8. We examine how the Earth's space environment dynamics evolves during both ICME events from both global and local perspectives, using well-established empirical models and in situ measurements as references. We show that on the large scale, and during moderate driving, the GUMICS-4 results are in good agreement with the reference values. However, the local values, especially during high driving, show more variation: such extreme conditions do not reproduce local measurements made deep inside the magnetosphere. The same appeared to be true when the event was run with another global simulation. The cross-polar cap potential (CPCP) saturation is shown to depend on the Alfven-Mach number of the upstream solar wind. However, care must be taken in interpreting these results, as the CPCP is also sensitive to the simulation resolution.